Shpet, Humboldt, Kant: Forms, Concepts, Schemes. Terms and Ideas - Victor I. Molchanov (Кантовский сборник)
The article examines the interpretation of the teaching of Wilhelm von Humboldt on language by Gustav Shpet together with Shpet’s perception of the influence of Kant’s philosophy on Humboldt. Special emphasis is laid on terminological analysis, the underlying thesis of this analysis being that words, terms and concepts are not the same thing: one and the same word or word combination can denote different terms, and the concept is a term in each particular doctrine. The object of critical analysis is the function of Humboldt’s term “inner form of language” and the way this term was transformed, according to Shpet, into “the concept of inner form” over time by various thinkers — Plato, Plotinus, Goethe, Humboldt and others. The difference is analysed between the terms which Humboldt, Shpet and Kant denoted by the same word “concept”. Shpet’s position on the issue of Kant’s influence on Humboldt is analysed, notably in terms of the “schematism of the pure concepts of understanding”. Steinthal’s opinion on this issue allows us to raise the hermeneutic question of what kind of Kant a particular researcher is dealing with at a particular time — from the beginning of the nineteenth century until our days. The author notes the peremptory character of some of Shpet’s claims as well as his description of Kant’s influence on Humboldt as suggestion. The author also considers Shpet’s critique of subjectivism, which robs subjectivism of creativity and confines it to the capacity to convey what has been understood and to err. Finally, Shpet’s methodology (the question of identity and difference) and the role of terminology in his own works is considered. The positing of identity as the starting point of method accords with Shpet’s conviction that terms have meaning and explanatory power. Contrary to Shpet, it is difference that is the initial experience and the key term in phenomenological and post-phenomenological philosophy.